A Comprehensive Taxonomy and Analysis of IEEE 802.15.4 Attacks. (26th July 2016) - Amin, Yasmin M.; Abdel-Hamid, Amr T.
Abstract : The IEEE 802.15.4 standard has been established as the dominant enabling technology for Wireless Sensor Networks (WSNs). With the proliferation of security-sensitive applications involving WSNs, WSN security has become a topic of great significance. In comparison with traditional wired and wireless networks, WSNs possess additional vulnerabilities which present opportunities for attackers to launch novel and more complicated attacks against such networks. For this reason, a thorough investigation of attacks against WSNs is required. This paper provides a single unified survey that dissects all IEEE 802.15.4 PHY and MAC layer attacks known to date. While the majority of existing references investigate the motive and behavior of each attack separately, this survey classifies the attacks according to clear metrics within the paper and addresses the interrelationships and differences between the attacks following their classification. The authors' opinions and comments regarding the placement of the attacks within the defined classifications are also provided. A comparative analysis between the classified attacks is then performed with respect to a set of defined evaluation criteria. The first half of this paper addresses attacks on the IEEE 802.15.4 PHY layer, whereas the second half of the paper addresses IEEE 802.15.4 MAC layer attacks.